2011
DOI: 10.1016/j.nlm.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Differential acetylcholine release in the prefrontal cortex and hippocampus during pavlovian trace and delay conditioning

Abstract: Pavlovian trace conditioning critically depends on the medial prefrontal cortex (mPFC) and hippocampus (HPC), whereas delay conditioning does not depend on these brain structures. Given that the cholinergic basal forebrain system modulates activity in both the mPFC and HPC, it was reasoned that the level of acetylcholine (ACh) release in these regions would show distinct profiles during testing in trace and delay conditioning paradigms. To test this assumption, microdialysis probes were implanted unilaterally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 77 publications
2
7
0
Order By: Relevance
“…Applied to classical eyeblink conditioning, the model is correctly able to account for the findings that, in intact animals, learning is slower as the ISI increases (also see Servatius, et al, 2001), that for a given ISI delay CRs are acquired faster than trace CRs, and that some (but not all) neurons in the hippocampus show activity patterns that predict and precede the form of the behavioral CR. Our model is also in agreement with studies showing that the hippocampus participates in appetitive (Flesher, Butt, & Kinney-Hurd, 2011; Seager, Asaka, & Berry, 1999) and fear (Esclassan, Coutureau, Di Scala, & Marchand, 2009) trace conditioning.…”
Section: - Discussionsupporting
confidence: 92%
“…Applied to classical eyeblink conditioning, the model is correctly able to account for the findings that, in intact animals, learning is slower as the ISI increases (also see Servatius, et al, 2001), that for a given ISI delay CRs are acquired faster than trace CRs, and that some (but not all) neurons in the hippocampus show activity patterns that predict and precede the form of the behavioral CR. Our model is also in agreement with studies showing that the hippocampus participates in appetitive (Flesher, Butt, & Kinney-Hurd, 2011; Seager, Asaka, & Berry, 1999) and fear (Esclassan, Coutureau, Di Scala, & Marchand, 2009) trace conditioning.…”
Section: - Discussionsupporting
confidence: 92%
“…Flesher, Butt, and Kinney-Hurd (2011) systematically compared ACh release measured by microdialysis probes in hippocampus and mPFC during appetitive trace and delay conditioning. The results showed that ACh release in both structures was correlated with trace but not delay conditioning performance (Flesher et al, 2011). The similarity between the effects of scopolamine in hippocampus and mPFC is also consistent with evidence for the coordination of tonic ACh release in dorsal hippocampus and mPFC during performance of a rewarded working memory task (Teles-Grilo Ruivo et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…Aversive trace conditioning has been more extensively studied, particularly in relation to the role of hippocampus in trace but not delay conditioning (Solomon et al 1986 ; Moyer et al 1990 ; Gabrieli et al 1995 ; Weitemier and Ryabinin 2004 ; Misane et al 2005 ), but with appropriate training parameters, a role for hippocampus in appetitive trace conditioning can also be demonstrated (Chan et al 2014 ). Whilst a microdialysis study has shown that ACh release, in both mPFC and hippocampus, was greater during appetitive trace conditioning than during delay conditioning (Flesher et al 2011 ), to our knowledge, there has been little previous work on the role of mPFC in appetitive trace conditioning.…”
Section: Discussionmentioning
confidence: 93%